Корпоративна соціальна відповідальність в системі мотивації праці - Антоненко, Н. В.; Antonenko, N. (ЦНТУ, 2019)
Стаття присвячена дослідженню актуальних питань корпоративної соціальної відповідальності бізнесу, що має вплив не тільки на стан соціально орієнтованої практики в системі мотивації праці, а і на сталий розвиток суспільства. Визначена сутність поняття “корпоративна соціальна відповідальність”, розглянуті теорії “корпоративного егоїзму”, “корпоративного альтруїзму”, “розумного егоїзму”. Запропоновані критерії, відповідність яким дозволяє вважати будь-який суб’єкт господарювання соціально відповідальним. Статья посвящена исследованию актуальных вопросов корпоративной социальной ответственности бизнеса, влияющей не только на состояние социально ориентированной практики в системе мотивации труда, а и на устойчивое развитие общества. Определена сущность понятия "корпоративная социальная ответственность", рассмотрены теории "корпоративного эгоизма", "корпоративного альтруизма", "разумного эгоизма". Предложены критерии, в случае соответствия которым любого субъекта хозяйствования можно считать социально ответственным. The article deals with topical issues of researching corporate social responsibility of business, which has an impact not only on the state of socially oriented practice in the system of work motivation, but also on the sustainable development of society. The purpose of the article is to investigate the theoretical and methodological foundations of corporate social responsibility formation in the system of work motivation of the personnel of enterprises of different forms of ownership. The essence of the concept of "corporate social responsibility" is defined, the approaches to understanding of corporate social responsibility by the level of perception of the idea of social responsibility are considered in detail: "corporate selfishness", "reasonable selfishness", "corporate altruism". It has been proven that there are a number of national models of corporate social responsibility, of which the European, British, American and Japanese corporate social responsibility systems are most prevalent. It is proposed to monitor and control the corporate social responsibility of the company by the following groups of indicators: integrated indicators of company behavior in the market; indicators of social responsibility to the staff; a group of indicators characterizing the degree of environmental pollution; indicators of the degree of involvement of business in public life. The study identifies the criteria that allow any economic entity to be considered socially responsible, namely: timely and full payment of taxes, compliance with the requirements of legislation at different levels; production and sale of quality products; implementation of training programs for employees; implementation of corporate medical programs on employee health and disease prevention; implementation of corporate programs of moral incentive for company employees; implementation of sponsorship and charity projects; measures to form a positive public opinion about business. It is noted that for today in Ukraine the social report is prepared in a free form according to indices determined independently by the organization. The format of such reporting does not allow us to summarize the corporate social responsibility indicators of companies in the city, in the region, in the industry as a whole. In Ukraine, there are currently no scientifically sound criteria for assessing corporate social responsibility, and this, in turn, requires clarification of wording, definition of integral indicators of the state of development of social orientation of companies. Thus, one area of further research is the unification of non-financial social reports (corporate social responsibility reports).
Корпоративная социальная ответственность в системе мотивации труда
Corporate Social Responsibility in the System of Labor Motivation
Keywords: корпоративна соціальна відповідальність; мотивація персоналу; соціальне партнерство; соціальна орієнтація; корпоративная социальная ответственность; мотивация персонала; социальное партнерство; социальная ориентация; corporate social responsibility; staff motivation; social partnership; social orientation